2023
DOI: 10.3389/fimmu.2023.1094764
|View full text |Cite
|
Sign up to set email alerts
|

Changes of tumor microenvironment in non-small cell lung cancer after TKI treatments

Abstract: Non-small cell lung cancer (NSCLC) is the most common lung cancer diagnosis, among which epidermal growth factor receptor (EGFR), Kirsten rat sarcoma (KRAS), and anaplastic lymphoma kinase (ALK) mutations are the common genetic drivers. Their relative tyrosine kinase inhibitors (TKIs) have shown a better response for oncogene-driven NSCLC than chemotherapy. However, the development of resistance is inevitable following the treatments, which need a new strategy urgently. Although immunotherapy, a hot topic for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 117 publications
0
7
0
Order By: Relevance
“…Many targeted therapies, including osimertinib, can be cytostatic in vitro but cause tumor regression in vivo (69) . In a complete biological system in vivo , EGFR disruption upregulates pro-inflammatory stress pathways, leading to inflammatory cytokine secretion, immune cell infiltration, and reduction of regulatory T cells, all of which support an anti-tumor response (70) . Likewise, TKIs can show cytostatic activity in vitro at doses that are selective for their target (as seen in osimertinib in H1975 cells at lower doses [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many targeted therapies, including osimertinib, can be cytostatic in vitro but cause tumor regression in vivo (69) . In a complete biological system in vivo , EGFR disruption upregulates pro-inflammatory stress pathways, leading to inflammatory cytokine secretion, immune cell infiltration, and reduction of regulatory T cells, all of which support an anti-tumor response (70) . Likewise, TKIs can show cytostatic activity in vitro at doses that are selective for their target (as seen in osimertinib in H1975 cells at lower doses [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that adequate immune infiltration and CD8 + T cell differentiation are also important in suppressing the development of metastasis [ 27 ]. Additionally, it has been reported that tumor tissue-resident memory CD8 + T cells are protective against cancer development by secreting various cytokines and/or triggering tumor cell death to maintain tumor-immune balance [ 11 ]. Although there are various subtypes of CD4 + T cells, these cells have different and even opposing effects that suppress or stimulate tumor development [ 1 , 7 , 11 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that tumor tissue-resident memory CD8 + T cells are protective against cancer development by secreting various cytokines and/or triggering tumor cell death to maintain tumor-immune balance [ 11 ]. Although there are various subtypes of CD4 + T cells, these cells have different and even opposing effects that suppress or stimulate tumor development [ 1 , 7 , 11 , 23 ]. According to the study by Chen et al, TILs were found to increase after neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, EGFR-TKIs can increase T cell–mediated tumor death by potentiating MHC class I and II molecule activation in response to interferon γ [ 10 , 11 ]. Although TME changes induced by EGFR-TKI therapy could determine the treatment efficacy [ 12 ], very few studies have focused on such changes in the preclinical models. Herein, we not only report the clinical results of a phase II trial of neoadjuvant/adjuvant erlotinib therapy among patients with stage II/IIIA EGFRm NSCLC but also analyze the TME changes induced by erlotinib.…”
Section: Introductionmentioning
confidence: 99%